EFFECTIVENESS OF AIR PRESSURE ON INCREASING FLUID FLOW RATE IN A TANK-BASED PIPELINE SYSTEM - Trissan, Whendy; Wiyogo; Lola Cassiophea; Ni Putu Diah Agustin Permanasuri; Mega Kurniawati; Topan Eka Putra; Via Lorenza; Clara Olivia Natalia (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
In simple water distribution systems, one of the main challenges often encountered is the slow flow of water from the storage tank to the point of use, especially in gravity systems that lack additional pumps. Water flow rate is significantly influenced by water level (head pressure), pipe diameter, and internal pressure within the system. Low water flow can disrupt the efficiency of water utilization for household, agricultural, and other technical purposes. This study aims to evaluate the effectiveness of air pressure in increasing water flow from a storage tank through a closed pipe system. This research also contributes to the development of simple, efficient water distribution technology that can be implemented in remote areas or areas with limited infrastructure. This research is a quantitative experimental study aimed at determining the effect of air pressure on water flow in the pipe system from the storage tank. The research was conducted at the Building Engineering Education Laboratory, Faculty of Teacher Training and Education, Palangka Raya University. Specific plans and targets include publication of this research in a SINTA-accredited journal, HKI, and a research video